Evolution of the preservation and restoration approach on built heritage:Martin Fabbri’s experience in peru - Gambetta Sponza, María Alexandra (2019)
This article analyzes an in-depth interview with restoration architect Martin Fabbri, carried out in 2017. It shows the expressions of restoration architecture, and the actions executed in it, while contrasting the discipline with some of the international charters and documents on the subject, in order to understand how this scholar combines theory and experience to achieve adequate and sustainable heritage conservation and restoration interventions according to current international standards and Peruvian reality. To achieve this, the article mentions national and international examples that show the influence of prominent thinkers, and international treaties and charters, in the protection and management of monuments. The above-mentioned is crucial to understand Fabbri's professional development as a restoration architect; the concepts he develops and the criteria he uses to work with Peruvian heritage, which can still be observed in some of his most outstanding works.